Behavioral Observations in Northern UGANDA: Development of a Coding System to Assess Mother–Child Interactions in a Post-war Society - Möllerherm, Julia; Wieling, Elizabeth; Saile, Regina; Forgatch, Marion Sue; Neuner, Frank; Catani, Claudia (Frontiers in Psychology, 2019)
There is growing interest in causes and consequences of disruptions in parent-child relationships in post-war environments. Recent studies mainly relied on self-reports to gain information about family dynamics following war exposure. Considering the limitations of self-report measures, we see the need for an in-depth examination of post-conflict parenting based on observational and quantitative data. The aim of the present study was the development of a coding system for a culturally bound description of parent-child interactions in northern Uganda, where virtually the entire population has been severely affected by twenty years of civil war. Interactions of 106 mothers and their 6- to 12-year-old children were observed during five structured interaction tasks. Foundation for the development of the coding system was the Family and Peer Process Code (FPP code). The cultural adaptation of the FPP code was based on in-depth qualitative analyses of a problem solving task, including a combination of inductive and deductive latent content analyses of textual data and videotapes, member checking and consultations of experts in the field of behavioral observations. The final coding system consists of 35 exhaustive and mutually exclusive content codes including codes for verbal, vocal, and compliance behavior as well as 14 affect codes. Findings indicate that the assessment of behavioral observations in post-conflict settings provides unique insights into culture- and context-specific interaction patterns and may be critical for the development and evaluation of parenting interventions.